Ozoralizumab, a Humanized Anti-TNFα NANOBODY® Compound, Exhibits Efficacy Not Only at the Onset of Arthritis in a Human TNF Transgenic Mouse but Also During Secondary Failure of Administration of an Anti-TNFα IgG - Ishiwatari-Ogata, Chihiro; Kyuuma, Masanao; Ogata, Hitoshi; Yamakawa, Machi; Iwata, Katsuya; Ochi, Motoki; Hori, Miyuki; Miyata, Noriyuki; Fujii, Yasuyuki (Frontiers in Immunology, 2022)
Although the introduction of tumor necrosis factor (TNF) inhibitors represented a significant advance in the treatment of rheumatoid arthritis (RA), traditional anti-TNFα antibodies are somewhat immunogenic, and their use results in the formation of anti-drug antibodies (ADAs) and loss of efficacy (secondary failure). Ozoralizumab is a trivalent, bispecific NANOBODY® compound that differs structurally from IgGs. In this study we investigated the suppressant effect of ozoralizumab and adalimumab, an anti-TNFα IgG, on arthritis and induction of ADAs in human TNF transgenic mice. Ozoralizumab markedly suppressed arthritis progression and did not induce ADAs during long-term administration. We also developed an animal model of secondary failure by repeatedly administering adalimumab and found that switching from adalimumab to ozoralizumab was followed by superior anti-arthritis efficacy in the secondary-failure animal model. Moreover, ozoralizumab did not form large immune complexes that might lead to ADA formation. The results of our studies suggest that ozoralizumab, which exhibited low immunogenicity in the animal model used and has a different antibody structure from that of IgGs, is a promising candidate for the treatment of RA patients not only at the onset of RA but also during secondary failure of anti-TNFα treatment.